2008
DOI: 10.1128/jvi.00142-08
|View full text |Cite
|
Sign up to set email alerts
|

Previously Infected Chimpanzees Are Not Consistently Protected against Reinfection or Persistent Infection after Reexposure to the Identical Hepatitis C Virus Strain

Abstract: Protective immunity after resolved hepatitis C virus (HCV) infection has been reported. However, the breadth of this immunity has remained controversial, and the role of neutralizing antibodies has not been well-defined. In the present study, two chimpanzees (CH96A008 and CH1494) with resolved monoclonal H77C (genotype 1a) infection were rechallenged with low-dose homologous H77C virus about 12 months after viral clearance; CH96A008 became persistently infected, and CH1494 had transient viremia lasting 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 36 publications
4
75
0
Order By: Relevance
“…In addition, the importance of both CD4 + and CD8 + memory T cells for protection against persistent HCV infection has been demonstrated by depletion studies performed in experimentally infected chimpanzees (10,11). The significance of the cellular immune response is further underscored by the fact that experimentally infected chimpanzees were found to be protected against repeated rechallenges in the absence of neutralizing Abs (12). Studies of other chronic viral infections indicate that, in addition to the frequency and specificity of the CD4 + and CD8 + T cells, the ability of the virusspecific memory cells to simultaneously produce multiple antiviral cytokines (IFN-g, TNF-a, and IL-2) might be associated with good viral control (13)(14)(15).…”
mentioning
confidence: 99%
“…In addition, the importance of both CD4 + and CD8 + memory T cells for protection against persistent HCV infection has been demonstrated by depletion studies performed in experimentally infected chimpanzees (10,11). The significance of the cellular immune response is further underscored by the fact that experimentally infected chimpanzees were found to be protected against repeated rechallenges in the absence of neutralizing Abs (12). Studies of other chronic viral infections indicate that, in addition to the frequency and specificity of the CD4 + and CD8 + T cells, the ability of the virusspecific memory cells to simultaneously produce multiple antiviral cytokines (IFN-g, TNF-a, and IL-2) might be associated with good viral control (13)(14)(15).…”
mentioning
confidence: 99%
“…the type of biopsy (such as needle, laparoscopic, or surgical biopsy) was usually not specified. In the case of long-running studies (Goncalvez et al, 2008), a chimpanzee might be subjected to dozens of liver biopsies or other tissue biopsies (Bukh et al, 2008).…”
Section: Tissue Samples and Biopsiesmentioning
confidence: 99%
“…HIV and hepatitis were by far the most frequent pathogens used in this manner (Wang et al, 1999;Bukh et al, 2008). Others included smallpox, Dengue fever, anthrax, human t-cell lymphoma virus (HtlV), herpes, respiratory syncytial virus, tuberculosis, encephalitis, and malaria (Chen et al, 2006a,b;Men et al, 2004;Arp et al, 1996;Blewett et al, 1999;Crowe et al, 1994;Franzoso et al, 1993;Goncalvez et al, 2008;Klotz et al, 1996).…”
Section: Infectious Agentsmentioning
confidence: 99%
“…Studies in reinfected chimpanzees that previously cleared the infection have revealed the existence of a protective immunity, which may, however, not be able to consistently prevent reinfection (Bukh et al, 2008;Major et al, 2002). The protection seems to be T-cell-mediated (reviewed by Bowen & Walker, 2005).…”
Section: Chimpanzee Model: Adaptive Immune Responsesmentioning
confidence: 99%
“…Interestingly, humoral immunity does not seem to be associated with HCV clearance in chimpanzees (Bartosch et al, 2003;Bukh et al, 2008;Cooper et al, 1999;Major et al, 1999Major et al, , 2004Thimme et al, 2002). One possible explanation is that titres of anti-hypervariable region 1 (HVR1) antibody, an antibody to the critical neutralization domain of E2 protein (Farci et al, 1996), do not correlate well with titres of HCV-specific neutralizing antibodies in vivo (Bartosch et al, 2003;Major et al, 1999).…”
Section: Chimpanzee Model: Adaptive Immune Responsesmentioning
confidence: 99%